Production, Characterization and Application of Inulinase from Pseudozyma sp. CCMB 300. - Assis, Sandra A.; Nascimento, Diego Sampaio; Lima, Danyo M.; Junior, Gildomar Valasques; Oliveira, Rodrigo de Queiroz; Fernandes, Pedro; Ribeiro, Rita de Cássia L. Figueiredo; Uetanabaro, Ana Paula Trovatti; Góes-Neto, Aristóteles (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The use of inulinases provides an alternative way to obtain fructose syrup through the hydrolysis of inulin. The objective of this work was to study the production, characterization and application of an inulinase from Pseudozyma sp CCMB 300 isolated from Brazilian semi-arid region. The higher production of inulinase in a medium containing 0.86 g L-1 yeast extract and 14.54 g L-1 glucose using response surface methodology (RSM). This statistical method was also used to access the optimum pH (8.28) and temperature (54ºC) for fermentative inulinase production. The results showed that the inulinase has potential for inulin hydrolysis, where a conversion yields of roughly 87.39 % for an initial concentration of inulin of 1% (w/v).